Accelerated forgetting in temporal lobe epilepsy: When does it occur?. (August 2021) - Contador, Israel; Sánchez, Abraham; Kopelman, Michael D.; González de la Aleja, Jesús; Ruisoto, Pablo
Abstract: Objective: The main goal of the study was to analyse differences in the forgetting rates of Temporal Lobe Epilepsy (TLE) patients at different intervals (30 sec, 10 min, 1 day and 1 week) compared with those of healthy controls. A secondary aim of this research was to provide an assessment of the relationship between clinical epilepsy-related variables and forgetting rates in TLE patients. Method: The sample was composed of 14 TLE patients and 14 healthy matched controls. All participants underwent a full standardised neuropsychological assessment including general intelligence, executive functioning, memory, language and other variables, such as depression, anxiety or everyday memory failures. Two specific memory tasks, consisting of cued recall of 4 short stories and 4 routes, were carried out at four different intervals. Results: There was a significant difference between groups at 10-min interval on the stories task, with the TLE group displaying greater forgetting than healthy controls. None of the other intervals on either task showed significant group differences. No differences were found when controlling for clinical epilepsy-related variables. Conclusion: Forgetting of verbal information at 10 min was greater in patients with TLE compared with controls, but accelerated longer term forgetting was not found. This study suggests that a late consolidation process is not necessarily impaired in TLE patients.